Analisis Kerusakan Komponen Sistem Power Train Menggunakan Root Cause Failure Analysis (RCFA) pada PT. Cipta Kridatama Samarinda - Muhammad Rafi’i; Mad Yusup; Purbawati Purbawati; Ida Rosanti; Diyaa Aaisyah Salmaa Putri Atmaja (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze the causes of component failure in the Power Train system of unit OHT773E CO2278 at PT. Cipta Kridatama, Samarinda, using the Root Cause Failure Analysis (RCFA) method. The Power Train system is responsible for transferring power from the engine to the final drive and other components, making it critical for the operational success of heavy equipment. Therefore, optimal maintenance is essential to prevent fatal failures that could impact the unit's performance. Based on the analysis, the dominant cause of failure is human factors, particularly technician negligence during component installation. This negligence results from a lack of understanding of the procedures and specifications recommended by the manufacturer, leading to incorrect installation of components. This failure impacts the achievement of the component’s expected lifetime, thus shortening the operational life of the components and increasing the risk of more severe damage. This also leads to higher repair costs and reduced unit productivity, resulting in longer downtime. To address this issue, several preventive measures are recommended, such as regular training for technicians to enhance their understanding of correct procedures and specifications, as well as the importance of following manufacturer guidelines during every maintenance and installation process. Additionally, it is advised to conduct routine discussions between technicians and supervisors to ensure that every maintenance step and installation complies with the established procedures. Increased oversight of the installation and maintenance process is also necessary, along with periodic rejuvenation of components to ensure the optimal performance of the Power Train system. Strengthening Preventive Maintenance (PM) practices is also crucial to minimize future damage potential. Implementing these solutions is expected to enhance the reliability of the Power Train system, extend component lifespan, and reduce failure frequency, ultimately improving the overall efficiency and productivity of the company.